Concerted actions to underline and promote the quality of wool and its products from local sheep breeds in Epirus - Nikolaou M.E.; Bellos G.K.; Pappas D.I. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
In Greece sheep are bred for milk (75% of income) and lamb meat (25%). Wool production, an internationally important production line, is nowadays considered worthless and in most cases, sheep wool is discarded resulting a burden for the environment. The aim of this study was to make known the actions that have been taking place in Epirus (Western Greece) since 2015, in order to underline the advantages of sheep wool from local breeds and to explore alternative uses for commercial exploitation. Firstly, Idea Generation Meetings between representatives of local agents (AGRCI and ATSBE) and the ATELIER “Wools of Europe” were held and a specific 5 year action plan was designed. Secondly, a number of wool quality analyses in three local sheep breeds (Katsika, Kalarrytiki and Frizarta, n=159) were carried out so as to explore the specific characteristics of their wool. Additionally, the “Sheep Wool Day 2017” festival was organized in Epirus, which included scientific conference, display of wool products, book and photo exhibition and children’s workshops relative to wool. Finally, the possibility of using wool from the above sheep breeds as an insulating material was investigated with encouraging results. Seeking new alternative uses of wool is expected to add value to the textile product and improve farmers’ income.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)